Mental Health Service Cultures and Reform Aspirations: What is Required for Change? - Ridley, Sophie Christina (Curtin University, 2022)
This research explored how mental health service cultures mediate Australian reform aspirations and activities. A qualitative research design was employed to explore the perspectives and experiences of mental health service users, families and practitioners. The research identified barriers to cultural change and the ways in which service cultures counteract, undermine and respond to reform and service improvement attempts. Key enablers and mechanism of cultural change are proposed based on the research findings.